CURVATURE, TORSION AND THE FRENET FRAME IN THE MATHEMATICA ENVIRONMENT - FAJKUS, Martin (Trends in education, 2013)
The article is dedicated to a program, which displays a user-defined 3D curve and calculates the curvature and the torsion at a chosen point of this curve. The user may let display tangent vector, normal vector and binormal vector at any point of the curve and also, for a good illustration, a small airplane flying along the curve as the user continuously changes its position by changing the value of the parameter of the curve.
Keywords: curvature; torsion; Frenet frame; Mathematica